A useful shift in our perspective: integrating social movement framing into social marketing. Issue 2 (10th April 2017) - Daellenbach, Kate; Parkinson, Joy
Abstract : Purpose: The elaboration of framing in social movement theory offers a different perspective than is typically taken in social marketing. This paper explores how social marketing may benefit from this alternate lens. Design/methodology/approach: The construction, features and processes associated with collective action frames in social movements are examined and explored via two social causes: obesity and disaster preparation. Findings: A social movement perspective on framing highlights the need to better understand variations in how groups may perceive a problem and its solutions. It suggests a range of considerations and options in constructing and participating in the development of collective action frames, which are suggested to benefit social marketing initiatives and, thus, society. Research limitations/implications: Further research in societal well-being and the meso-level of social change should consider adopting a social movement framing perspective. A list of questions is provided to guide future research. Practical implications: Mobilising a group into action is often a necessary and effective step in realising social change. The questions raised in social movement framing will equip practitioners and researchers with greater understanding of the issue, the context and potential solutions, ultimately to encourage positive social movements and social benefit. Originality/value: While calls have been made for broader perspectives in social marketing, little attention has been given to social movements. This paper offers a way forward with respect to framing.